Assessment of Information predictability of stochastic processes - A. V. Ausiannikau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The necessary theoretical information for parameter estimation algorithms informational predictability of stochastic processes. We consider examples of algorithms for estimating the predictability of information for the processes described by the optimal difference schemes, equivalent prognostic models in the form of stochastic differential equations.